Is MRA More Accurate In Diagnosing Cervical Vascular Injury In Trauma Patients Than CTA? - Almansour, Hamad Abayan S; Almansour, Mohammed Hussain Ali; Almansour, Mohammed Hamad Hadi; Almansour, Ali Hadi; Al-Mehthel, Ali Hussain Hamad; Alyami, Abdullah Hadi Abdullah; salem, Ahmed Abdullah Hussain Al; qufla, Yahya hamad marshad al (Migration Letters, 2023)
Aim The aim of this systematic review was to evaluate the diagnostic accuracy of magnetic resonance angiography (MRA) versus computed tomography angiography (CTA) for cervical vascular injury secondary to trauma. Background CTA is widely used in practice to diagnose cervical vascular injuries, largely supplanting the gold standard of digital subtraction angiography (DSA). However, the use of CTA is limited by the exposure to ionising radiation and lack of sensitivity in some contexts. Hence, evaluation of the potential diagnostic accuracy of MRA in this context is justified. Methods A systematic literature review was completed using online databases and a clear search strategy. Diagnostic accuracy studies involving the use of CTA and/or MRA in the diagnosis of cervical vascular injuries were sought, with a focus on human studies, primary studies and literature published between 2011 and 2021. Studies were subjected to formal critical appraisal using the Critical Appraisal Skills Programme toolkit and were synthesised using a narrative framework. Results The results of the literature search identified seven studies that met the review inclusion criteria. Five studies evaluated the diagnostic accuracy of CTA, noting sensitivity ranging from 51% to 72% for cervical vascular injury, high specificity (63–97%) and a high overall diagnosti[1]c accuracy (95%) compared with DSA. MRA diagnostic accuracy was not as robustly assessed in the two included studies, although evidence suggests consistency with expert consensus imaging and CTA/DSA imaging standards in specific contexts. No study directly compared CTA and MRA in the diagnosis of cervical vascular injury secondary to trauma. Conclusion These findings suggest that CTA remains the imaging strategy of choice for suspected cervical vascular injury, as MRA does not have evidence supporting use in this context. The practical use of CTA and availability of this imaging approach further supports its use in trauma contexts